ETR 300 : An-Nur GSM Sdn. Bhd. / Mohd Ezuwan Haris ... [et al ] - Haris, Mohd Ezuwan; Yahya, Muhamad Haizam; Tuan Kob, Syed Kassmaza; Sazali, Haslizal; Mohd Salleh, Mohd Adib Povera (2001)
Therefore An-Nur GSM Sdn. Bhd. will expand the promotion to inctease business turnover. As the results, An-Nur GSM Sdn. Bhd. services would be amplified and profit can be attained, thus the constantly demand for this service will ensure us a good profit in the future.